The Phenomenon of Trance in The Tradition of Kuda Lumping Arts in Jorong Wonorejo, Nagari Lubuk Gadang Selatan, South Solok Regency, West Sumatra Province - Pratama, Wahyu; Yurisman; Endrizal (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study discusses the "Trance Phenomenon in the Kuda Lumping Art Tradition in Jorong Wonorejo, Nagari Lubuk Gadang Selatan, Solok Selatan Regency, West Sumatra Province". The purpose of this study is to describe the procession and factors causing kuda lumping players to experience trance in Jorong Wonorejo. This study uses the phenomenological theory by Edmund Husserl, in this study supported by qualitative methods in order to describe the data from the field. The data collection techniques are field observation, interviews (in-depth interviews), and documentation. Data analysis techniques used in this study include data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that researchers found several processions in the kuda lumping tradition including, the preparation stage, the implementation stage, the event begins, and the last is the healing process, then there are several supporting tools such as, Gendang, Saron, Demung, Saron penyerang, Bonang, Bonang sukses, Kenong, Gong, Mask, Barongan, and the last is Pecut and Kuda- kudaan. There are several factors that influence the trance phenomenon in the kuda lumping tradition. The first factor is the factor of experiencing, the second is the spiritual factor, the third is the song and music factor. There are other interesting things in the form of the transition of endang which was originally fierce to endang with a funny character. This tradition has its own uniqueness, especially the trance phenomenon, which makes the Wonorejo community interested in witnessing this tradition